Survey of management practices used by brazilian dairy farmers and recommendations provided by 43 dairy cattle nutritionists - Silva, Diego P. [UNESP]; Pedroso, Alexandre M.; Pereira, Murillo C.S. [UNESP]; Bertoldi, Gustavo P. [UNESP]; Watanabe, Daniel H. M. [UNESP]; Melo, Alan C. B. [UNESP]; Millen, Danilo D. [UNESP] (Canadian Science Publishing, 2019)
This work aimed to survey management practices used by dairy farmers and to report nutritional recommendations adopted by 43 dairy cattle nutritionists in Brazil. The web-based survey consisted of 80 questions. Almost 50% of the participants had clients that produce <1000 kg of milk daily and 48.8% had clients who own fewer than 100 dairy cows. Corn was the primary source of grain (97.4%), and 43.9% of the nutritionists included from 41% to 50% concentrate in lactation diets. The mean roughage inclusion in lactation diets was 50.5% and 79% of the nutritionists reported corn silage as the primary roughage source. Average crude protein and rumen-degradable protein concentrations recommended by the nutritionists for lactation diets were 15.7% and 9%, respectively. Average Ca and P concentrations recommended for lactation diets were 0.70% and 0.41%, respectively. The major health problem reported by 83.9% of the nutritionists was mastitis. The present survey provides an overview of management practices adopted by dairy farmers and nutritional recommendations currently applied by dairy cattle nutritionists in Brazil. The most critical points identified were low milk yield, mastitis as the major health problem, lack of proper mixing and delivery of rations, and destination of male calves.
Keywords: Brazil; Dairy cow; Management; Nutrition; Survey